Performance of stocker heifers and steers grazing high endophyte fescue and offered oxytetracycline in a mineral mixture. - Coffey, K.; Brazle, F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to evaluate the performance of stocker calves grazing high-endophyte fescue (68 to 70%) and offered oxytetracycline in a free-choice mineral supplement. In Experiment 1, 24 yearling crossbred heifers were utilized in a 112-day grazing study beginning on June 18. Performance of both control calves and those receiving oxytetracycline was extremely poor, making data interpretation difficult. Average oxytetracycline consumption was 327 mg per head, daily. Approximately 8296 of the total grazing time occurred during the daylight hours (6arn - l0pm) for both treatment groups. Heifers offered the medicated mineral mix grazed 20 minutes more than heifers offered the control mineral mix. Hair scores and rectal temperatures were unaffected by oxytetracycline supplementation. In Experiment 2, fifty-three crossbred steers were utilized in an 83-day grazing study beginning on September 15. Steers were randomly divided into groups of 25 and 28. One group received a control mineral mixture, whereas the other received a similar mineral mix containing oxytetracycline, 250 mg per ounce. Steers fed oxytetracycline gained faster (P<.05) and tended to have lower (P=.12) rectal temperatures. Therefore, response of cattle to consumption of oxytetracycline from a mineral mixture may be variable. Heifers grazing endophyte infected tall fescue (Experiment 1) may not have gained sufficiently to support treatment differences. However, when cattle were gaining weight (Experiment 2), treatment differences were observed.
Keywords: Beef; Performance; Stocker heifers; Steers; High endophyte fescue; Oxytetracycline